Situation and Vector Analysis of Cognitive and Personality Development of Students in the Process of Overcoming Learning Difficulties - Zaretsky, V.K.; Nikolaevskaia, I.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2020)
During reflective-activity approach counseling sessions with students aimed at helping them overcome difficulties, there often occurs a phenomena of ‘explosive dynamics’ when significant qualitative changes happen, both in the cognitive and personality spheres. The multi-dimensional model of the zone of proximal development proposed in the reflective-activity approach makes it possible to theoretically substantiate and describe the mechanism of cognitive and personality development in the process of overcoming learning difficulties. While working out the parameters for analyzing the dynamics of cognitive and personality development of students, the following three main tasks had to be solved: 1) how to analyse the process of joint work of the student and the counselor to reconstruct the structural-dynamic picture of qualitative cognitive and personality changes from the session transcript (speech production); 2) how to show the dynamics of learning through the subject matter of the tasks, the dynamics of cognitive and personality lines of development; 3) how to capture the connection between psychotherapeutic and pedagogical help and positive qualitative cognitive and personality changes. We thus developed a method based on the principles and methods of speech production analysis in creative task solving which is considered an equivalent of learning difficulties. The paper discusses an example of the analysis of counselor-student interaction based on the developed method. which illustrates the ‘reflection’ dynamics that occurs during one session. При оказании учащимся помощи в преодолении трудностей средствами рефлексивно-деятельностного подхода нередко имеет место феномен «взрывной динамики», когда происходят существенные качественные изменения, как в когнитивном, так и в личностном плане. Разработанная в рамках рефлексивно-деятельностного подхода многовекторная модель зоны ближайшего развития дает возможность теоретически обосновать и описать механизм когнитивно-личностного развития в процессе преодоления учебных трудностей. При разработке метода анализа динамики когнитивно-личностного развития учащихся решались три основные задачи: как анализировать процесс совместной деятельности ученика и консультанта, чтобы по стенограмме занятия (речевой продукции) реконструировать структурно-динамическую картину качественных когнитивно-личностных изменений; как показать динамику движения в предметном содержании выполняемых заданий, динамику по векторам когнитивного и личностного развития; как установить, что именно психолого-педагогическая помощь консультанта учащемуся в ситуациях преодоления учебных трудностей способствует зафиксированной динамике. Разработанный метод ситуационно-векторного анализа опирается на принципы и методику анализа речевой продукции испытуемых при решении творческих задач, которые рассматриваются как аналог учебных трудностей. Приводится пример анализа ситуаций взаимодействия консультанта и ученика с использованием разработанного метода, который иллюстрирует динамику по вектору «рефлексия», происходящую в ходе одного учебного занятия.